The role of scale in integrating climate change adaptation and mitigation in cities - Landauer, Mia; Juhola, Sirkku; Klein, Johannes (Journal of environmental planning and management, 2019)
By using a scale framework, we examine how cross-scale interactions influence the implementation of climate adaptation and mitigation actions in different urban sectors. Based on stakeholder interviews and content analysis of strategies and projects relevant to climate adaptation and mitigation in the cities of Copenhagen and Helsinki, we present empirical examples of synergies, conflicts and trade-offs between adaptation and mitigation that are driven by the cross-scale interactions. These examples show that jurisdictional and institutional scales shape the implementation of adaptation and mitigation strategies, projects and tasks at the management scale, creating benefits of integrated solutions, but also challenges. Investigating the linkages between adaptation and mitigation through a scale framework provides new knowledge for urban climate change planning and decision-making. The results increase the understanding of why adaptation and mitigation are sometimes handled as two separate policy areas and also why attempts to integrate the two policies may fail.